2021
DOI: 10.20452/pamw.16049
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-treatment failure and peripheral eosinophils in non-small cell lung cancer patients treated with immune checkpoint inhibitors

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In addition to improved clinical outcomes, the increase in eosinophil counts after initiation of ICIs was also reported to be an early biomarker for the development of immune-related adverse events (irAEs). Osawa et al found that peripheral eosinophilia (defined as AEC ≥ 330/µL) at week 6 was associated with a 2.8-fold higher risk of irAEs [ 46 ]. Studies have observed such associations in ICI-induced adrenal insufficiency [ 47 ], hypopituitarism [ 48 ], cutaneous irAEs [ 49 ], and pneumonitis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improved clinical outcomes, the increase in eosinophil counts after initiation of ICIs was also reported to be an early biomarker for the development of immune-related adverse events (irAEs). Osawa et al found that peripheral eosinophilia (defined as AEC ≥ 330/µL) at week 6 was associated with a 2.8-fold higher risk of irAEs [ 46 ]. Studies have observed such associations in ICI-induced adrenal insufficiency [ 47 ], hypopituitarism [ 48 ], cutaneous irAEs [ 49 ], and pneumonitis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…possibly due to the small number of participants. A previous study showed that the time to treatment failure and the survival time were longer in patients with a higher eosinophil level during ICI treatment and at baseline (21,26,34). The potential mechanism may be that eosinophils strengthened the antitumor response by normalizing the tumor vessels and enhancing the infiltration of CD8(+) T cells in caner tissues (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…cancer patients. 15,17 In NSCLC patients, ICI therapy only induces an early increase in blood eosinophils, which is more prominent in responding patients. 16 An increased REC during ICI therapy correlated with more objective responses.…”
Section: Discussionmentioning
confidence: 99%
“…14 In lung cancer patients, ICI-treated NSCLC patients with eosinophilia during treatment had higher response rates (RR) and more prolonged treatment durations. [15][16][17][18] OS is the most robust indicator of cancer treatment outcomes. Nevertheless, the relationship between an increased REC and OS in lung cancer patients treated with ICIs has not yet been examined in detail.…”
Section: Introductionmentioning
confidence: 99%